2016
DOI: 10.1016/j.jelechem.2015.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of carbon based electrodes from pyrolyzed paper for biosensing applications

Abstract: This article details the study of electrochemical behavior of new carbon electrodes based on pyrolysis of different paper sources to be used in biosensor applications. The resistivity of the pyrolyzed papers was initially used as screening parameters to select the best three paper samples (imaging card paper, multipurpose printing paper, and 3MM chromatography paper) and assemble working electrodes that were further characterized by a combination of microscopy, electrochemistry, and spectroscopy. Although slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 69 publications
3
45
0
4
Order By: Relevance
“…The resistivity of the carbonized samples was calculated using the resistance values measured using a standard digital multimeter (2216-20 TRMS, Milwaukee Electric Tool Corp.; Brookfield, WI) and the procedure previously described [39]. In order to improve the electrical contact with the multimeter connectors, silver paint was applied on the CuNPs-modified pyrolyzed samples by displaying silver contacts with a gap of 1 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistivity of the carbonized samples was calculated using the resistance values measured using a standard digital multimeter (2216-20 TRMS, Milwaukee Electric Tool Corp.; Brookfield, WI) and the procedure previously described [39]. In order to improve the electrical contact with the multimeter connectors, silver paint was applied on the CuNPs-modified pyrolyzed samples by displaying silver contacts with a gap of 1 cm.…”
Section: Resultsmentioning
confidence: 99%
“…As a modification from a recent publication from our group [39], CuNPs@CEs were obtained by pyrolysis of paper strips (JP40 filter paper, 80 g·m −2 , Quanty; J-Prolab, Brazil) of 1.5 cm × 3.5 cm modified with a solution containing CuSO 4 . The advantages and limitations of this method (rendering bare carbon electrodes) were described in the aforementioned report.…”
Section: Methodsmentioning
confidence: 99%
“…Heating cellulose paper to high temperatures (1000 C), without the presence of oxygen, creates a dense carbon material. 38 Garcia et al have demonstrated that pyrolyzing paper, under reductive conditions, produces carbonized cellulose fibers. These fibers have been decorated with CuNPs and used as electrodes.…”
Section: ·2 Modification Of Cellulose Papermentioning
confidence: 99%
“…[13] Alternatively, nanoporous thin films of gold can be prepared by dissolving silver from a film of a silver-gold alloy. [15] Other methods used carbon-based polymeric materials, such as paper and polymeric fibers, as templates for the fabrication of (i) porous, conductive structures of carbon [19] and (ii) porous structures of metal oxides (e.g., TiO 2 , MnO 2 , Fe 2 O 3 ). [20][21][22][23][24] For example, Garcia and co-workers prepared conductive carbon paper by heating paper at 1000 °C in slightly reducing conditions (95% Ar-5% H 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] For example, Garcia and co-workers prepared conductive carbon paper by heating paper at 1000 °C in slightly reducing conditions (95% Ar-5% H 2 ). [19] www.advancedsciencenews.com Figure 1. A,B) Photographs of the paper template (A) used to produce the paper-templated gold structure (B).…”
Section: Introductionmentioning
confidence: 99%